1989
DOI: 10.1056/nejm198908173210704
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of a Relation between the Periconceptional Use of Vitamins and Neural-Tube Defects

Abstract: Whether taking multivitamins or folate around the time of conception can reduce a woman's risk of having a child with a neural-tube defect is controversial. To investigate this question, we examined the periconceptional use of vitamin supplements by women who had a conceptus with a neural-tube defect (n = 571), women who had had a stillbirth or a conceptus with another malformation (n = 546), and women who had had a normal conceptus (n = 573). Women with conceptuses with neural-tube defects were identified eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(69 citation statements)
references
References 10 publications
0
68
0
1
Order By: Relevance
“…NTDs in such areas probably have a genetic basis or originates from other causes than a lack of folic acid . Furthermore, women who started the use of supplements after conception seem to be classi®ed as`non-users' (Mills et al, 1989), whereas other observational studies have indicated that folic acid can also be protective in this period (Milunsky et al, 1989;Bower & Stanley, 1989;Shaw et al, 1995). Other reasons could be the broad range of central nervous system defects that were included as cases in both studies (Winship et al, 1984;Mills et al, 1989).…”
Section: Developments Regarding Folate Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…NTDs in such areas probably have a genetic basis or originates from other causes than a lack of folic acid . Furthermore, women who started the use of supplements after conception seem to be classi®ed as`non-users' (Mills et al, 1989), whereas other observational studies have indicated that folic acid can also be protective in this period (Milunsky et al, 1989;Bower & Stanley, 1989;Shaw et al, 1995). Other reasons could be the broad range of central nervous system defects that were included as cases in both studies (Winship et al, 1984;Mills et al, 1989).…”
Section: Developments Regarding Folate Requirementsmentioning
confidence: 99%
“…In two case-control studies the reduction in the risk of an NTD-affected birth was not signi®cant (Winship et al, 1984;Mills et al, 1989). The study of Winship et al, (1984) lacked information on the use of non-prescribed drugs (of which folic acid is a common one) and on the use of drugs prescribed by hospital physicians.…”
Section: Developments Regarding Folate Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…For women without a prior history of NTDs, 4 of 5 studies reported decreases of 40% to 100% if folic acid was taken on a daily basis. [3][4][5][6][7][8] For women with a prior history of NTDs, all published studies reported a similar reduction after folic acid supplementation. 9 -12 The dose of folic acid, either alone or part of a multivitamin preparation, varied between 400 to 5000 g (0.4 -5 mg) per day and was taken at least 1 month before conception and throughout the first trimester.…”
mentioning
confidence: 99%
“…by 30–70% (Laurence et al 1981; Smithells et al 1983; Mulinare et al 1988; Mills et al 1989; Milunsky et al 1989; MRC Vitamin Study Research Group 1991; Saitsu et al 2003), leading to an international consensus on the importance of preconceptional FA supplementation. In Japan, despite the efforts of JSOG and JAOG, preconceptional FA supplementation was not universally accepted.…”
Section: Communication Of Fa Intake Recommendationsmentioning
confidence: 99%